Immigrant and Refugee Families - Ballard, Jaime; Wieling, Elizabeth; Solheim, Catherine; Dwanyen, Lekie (Open textbook library., 2016)
Immigrant and Refugee Families: Global Perspectives on Displacement and Resettlement Experiences offers an interdisciplinary perspective on immigrant and refugee families' challenges and resilience across multiple domains, including economic, political, health, and human rights. This new edition has been revised and updated from the original 2016 edition. Co-edited with equal contribution by Jaime Ballard, Elizabeth Wieling, Catherine Solheim, and Lekie Dwanyen